Effort to Integrate Islamic Education Curriculum with Digital Literacy in Realizing the Sustainable Development Goals (SDGs) Program - Muh. Addarunnafis; Syarifah Aulia Rabbani; Asriati Aulia Malik (Jurnal Ilmiah Profesi Pendidikan, 2026)
The integration of the Islamic Education curriculum with digital literacy is crucial for strengthening moral values, ethics, and character amid the rapid advancement of digital technology. Furthermore, Indonesia still faces challenges in digital literacy, particularly regarding digital culture, making educational innovation essential to support the achievement of the 2030 Sustainable Development Goals (SDGs). This study aims to analyze efforts to integrate the PAI curriculum with digital literacy in support of achieving the SDGs, particularly regarding the improvement of educational quality. This study employs a library research method using a qualitative descriptive approach through the analysis of relevant scientific journals, books, and online news sources. The results of the study reveal seven strategic efforts, namely: 1) intensive training for educators, 2) the inclusion of digital literacy in learning, 3) the development of digital competencies, 4) the utilization of digital-based learning resources, 5) the implementation of digital projects, 6) the strengthening of digital ethics, and 7) the development of a digital culture. These seven efforts are referred to as the “Sapta-Upaya” as a strategic framework for integrating the PAI curriculum with digital literacy. In conclusion, the integration of the PAI curriculum with digital literacy can contribute to supporting the achievement of the SDGs through the creation of quality, ethical education capable of competing globally without compromising moral and cultural values.